Coaching performance swimmers: the individualisation of training programmes in Great Britain - Cross, N.; Wright, I. (coachesinfo.com)
The aims of this ethnographic study were to elicit a broad base of data relating to swimming training individualisation. Initially, 88 questionnaires (60 responses) were distributed to elite swimming coaches working in the United Kingdom to elicit quantitative data on the following range of research questions: 1) Do elite swimming coaches individualise training programmes? 2) What measures do they take (if any) to effect this? 3) Are their swimmers treated differently depending on such factors as status, gender, age and experience? 4) What restrictions acting upon the coaching process affect the amount of individualisation? 5) What tensions arise because of this? Subsequently, the results from the questionnaires led to the formation of an additional in-depth interview schedule which was used to elicit more qualitative data through extended interviews with 18 prominent elite British swimming coaches. The findings of the research confirmed that the majority of the coaches used a variety of methods to individualise training. Despite all of the coaches recognising the importance of individualising training programmes, various constraints and restrictions limited the amount of individualisation actually possible. Thus, the individualisation process was seldom optimal and, even in situations where fewer constraints applied, it still did not appear to receive the importance it deserves.